REAKSI PASAR DI SEKITAR TANGGAL PENGUMUMAN LABA: PENGUJIAN ANALISIS TEKNIKAL MODERN - Dedhy Sulistiawan (University of Merdeka Malang, 2009)
The purpose of this research was to test the profitability of technical analysisindicators around annual earnings announcements date. Offering new technique to test marketreaction, this research preferred modern technical analysis to classical indicators because of theobjectivity of measurement. This research used Indonesian Stock Exchange data in year 2008.There were two technical indicators selected, they were RSI (5) and RSI (5)-SMA (5). Using onesample t-test, the results showed that this trading strategy was profitable around earningsannouncement date. It meant that signal could be used before announcement date. The datashowed that selling signal was statistically significant producing profit but not buying signal.Supplementary analysis results showed that there was no correlation between technical analysisreturn and earnings change. This phenomenon described that technical analysis was profitablebut data showed that there was evidence about the pattern of buying signal (selling signal)before good news (bad news).